12x-3y-2(4x+y)=

Simple and best practice solution for 12x-3y-2(4x+y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-3y-2(4x+y)= equation:


Simplifying
12x + -3y + -2(4x + y) = 0
12x + -3y + (4x * -2 + y * -2) = 0
12x + -3y + (-8x + -2y) = 0

Reorder the terms:
12x + -8x + -3y + -2y = 0

Combine like terms: 12x + -8x = 4x
4x + -3y + -2y = 0

Combine like terms: -3y + -2y = -5y
4x + -5y = 0

Solving
4x + -5y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5y' to each side of the equation.
4x + -5y + 5y = 0 + 5y

Combine like terms: -5y + 5y = 0
4x + 0 = 0 + 5y
4x = 0 + 5y
Remove the zero:
4x = 5y

Divide each side by '4'.
x = 1.25y

Simplifying
x = 1.25y

See similar equations:

| 2x-20=80 | | 7x+8y+3(2x+4y)= | | 5a+7a-6b-3a= | | 2(2n-3)=2n-2(n-1) | | m=4+m | | -5(-2x+3)= | | 7x-3y+9x-2y= | | Dx+9y=27 | | 5/8(x-7)=10 | | logv[12](x)+logv[12](11x-1)=1 | | 12x+5y=8400 | | 12x=6x+20-8 | | 5p+7s+4p-3s= | | 4x-32=9x+17 | | 15m^2-5m^2=30m+11m | | 7x+4y+2x-6y= | | 3x+7=5x-q | | 5x+12y=8400 | | 27=9s | | 10x-5=8x+15 | | (2x-3)/(5-3x)0 | | =(x+y-1)+(x+y+1)-(x+y-z) | | 4b-9b= | | 3x-20=x+8 | | 9+35r+25r=35r+34r | | x=3x^2+2x+6 | | F+2f+4f= | | x^2+y^2-10x+9y+1=0 | | 81/:5/6 | | 5p+3p+4p= | | x^2y^2-10x+9y+1=0 | | -16-(-38)=x/5 |

Equations solver categories